EFFECT OF INFORMATION COMMUNICATION TECHNOLOGIES (ICT) USAGE ON CASHEW NUT MARKETINGEFFICIENCY IN OYO STATE - Mohammed, O.O.; Adetunji, M.O.; Akande, K.B.; Oyedipe. O.B. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined the effects of ICT usage on cashew nut marketing efficiency in Oyo State. Amulti-stage sampling procedure sampling procedure was used to select a total of 200 respondents. Data were collected using structured questionnaires and analysed using both descriptive and inferential statistics. Findings showed that 88% of respondents were male, with an average age of 47 years. Most(85.5%) of the respondents had secondary education or higher, and 78% relied on cashew marketing as their main occupation, with an average experience of 16.9 years. ICT adoption was highest for mobile apps (92%) and WhatsApp (90%), moderate for Facebook (87.5%) and Instagram (54%), while Twitter and TikTok were not used. Cashew marketing was profitable, with a marketing margin of ₦27,941.46 and MER of 1.333. The findings show that age, marital status, marketing experience, primary occupation, marketing type, and social influence are not significant determinants of ICT use (p > 0.05). In contrast, sex, education level, household size, ICT training, and access to credit significantly influence ICT adoption (p < 0.05), indicating that capacity-building and resource-related factors drive ICT use The study recommends subsidized ICT tools, targeted training, more credit access, and stronger digital infrastructure.